1993
DOI: 10.1046/j.1537-2995.1993.33393174450.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractoriness to platelet transfusion by protein A column therapy

Abstract: Ten thrombocytopenic patients (platelets < 10-24 x 10(9)/L) who were refractory to platelet transfusion were investigated for their responsiveness to staphylococcal protein A column therapy. Nine patients had previously been treated with steroids, intravenous immune globulin, and/or other forms of immunosuppressive therapy without improvement in their transfusion response. All patients were receiving multiple platelet transfusions without achieving 1-hour corrected count increments (CCIs) > or = 7500. Eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 47 publications
(3 reference statements)
0
18
0
Order By: Relevance
“…The results of these studies are not uniform. Lopez–Plaza et al [90]found no beneficial effect of PAIA while Christie et al [91]found improvement in responsiveness to platelet transfusions. Patients with aplastic anaemia with haemorrhagic diathesis and infection risks, however, are not ideal candidates for this approach.…”
Section: Therapeutic Approaches In Platelet Transfusion Refractorinessmentioning
confidence: 99%
“…The results of these studies are not uniform. Lopez–Plaza et al [90]found no beneficial effect of PAIA while Christie et al [91]found improvement in responsiveness to platelet transfusions. Patients with aplastic anaemia with haemorrhagic diathesis and infection risks, however, are not ideal candidates for this approach.…”
Section: Therapeutic Approaches In Platelet Transfusion Refractorinessmentioning
confidence: 99%
“…1,2 Protein A immunoadsorption column composes of an activated carrier and protein A, which is bonding to the surface of the carrier. Agarose gel is the carrier of protein A immunoadsorption column and its activation reaction process in the stirred reactor is the key to achieve larger scale industrial production of blood purification materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nilsson et al have used protein A-linked agarose beads for removal of IgG from patients with chronic lymphocytic leukemia and autoimmune hemolytic anemia [11,12]. Recently, Chriestie et al have reported the treatment of refractoriness to platelet transfusion by protein A column therapy [13].…”
Section: Introductionmentioning
confidence: 99%